Dopamine D2 receptor stimulation modulates the balance between ignoring and updating according to baseline working memory ability. (October 2019) - Fallon, Sean James; Kienast, Annika; Muhammed, Kinan; Ang, Yuen-siang; Manohar, Sanjay G; Husain, Masud
Background: Working memory (WM) deficits in neuropsychiatric disorders have often been attributed to altered dopaminergic signalling. Specifically, D2 receptor stimulation is thought to affect the ease with which items can be gated into and out of WM. In addition, this effect has been hypothesised to vary according to baseline WM ability, a putative index of dopamine synthesis levels. Moreover, whether D2 stimulation affects WM vicariously through modulating relatively WM-free cognitive control processes has not been explored. Aims: We examined the effect of administering a dopamine agonist on the ability to ignore or update information in WM. Method: A single dose of cabergoline (1 mg) was administered to healthy older adult humans in a within-subject, double-blind, placebo-controlled study. In addition, we obtained measures of baseline WM ability and relatively WM-free cognitive control (overcoming response conflict). Results: Consistent with predictions, baseline WM ability significantly modulated the effect that drug administration had on the proficiency of ignoring and updating. High-WM individuals were relatively better at ignoring compared to updating after drug administration. Whereas the opposite occurred in low-WM individuals. Although the ability to overcome response conflict was not affected by cabergoline, a negative relationship between the effect the drug had on response conflict performance and ignoring was observed. Thus, both response conflict and ignoring are coupled to dopaminergic stimulation levels. Conclusions: Cumulatively, these results provide evidence that dopamine affects subcomponents of cognitive control in a diverse, antagonistic fashion and that the direction of these effects is dependent upon baseline WM.